GLOBALISASI: ANTARA PELUANG DAN ANCAMAN BAGI MASYARAKAT MULTIKULTURAL - Umar Sholahudin (Jurnal Sosiologi Pendidikan Humanis, 2019)
This article examines globalization, between opportunities and threats for Indonesia's multicultural society. Globalization has brought changes in the social, political, economic, and cultural life of the people, especially for multicultural Indonesians. The swift flow of globalization that continues to move through various lines of life of people and reduce the borders of nations. Globalization will bring two consequences at the same time for the Indonesian cultural community, namely how the opportunities and threats of globalization to Indonesia's multicultural society. This study uses a literature study approach, where data and information relevant to the topic or problem are subject to study and compiled from various scientific sources and other sources. The theoritical framework used in this study is the theory of cultural homogenization. The results of this literature study indicate that the current of globalization will pose a threat as well as an opportunity for Indonesia's multicultural society. An opportunity that can be exploited is the emergence of a collective awareness about living together in differences that are co-existent. Meanwhile, the threat that needs to be watched out for is the strengthening of cultural homogenization that can erode and uproot the roots of local culture. Therefore, Indonesian multicultural society is not only required to think and act more critically and intelligently in dealing with the various subversive and destructive effects of globalization, but more than that it is able to build diversity immunity